Severe acute pancreatitis - Samaniego, Castor; Frutos, Benito (Cirugía del Uruguay, 1996)
This study analyzes in retrospect the medica/ histories of 24 patients, chooses from a total of 280 cases of Acute Pancreatitis treated in the Service of Surgery, Clínicas Hospital, from 1980 to 1994. The patients had one ar more of the following: 3 ar more lmrie classification factors, an image of pancreatic ar peripancreatic necrosis, with ar without associated collection on CT, multiorgan fai/ure and metabolic disturbances requiring /CU ar findings of necrosis and / ar pancreatic ar peripancreatic infection on laparatomy.